A case of Timothy syndrome with adrenal medullary dystrophy. Issue 10 (4th September 2016) - Kawaida, Miho; Abe, Tokiya; Nakanishi, Toshio; Miyahara, Yoko; Yamagishi, Hiroyuki; Sakamoto, Michiie; Yamada, Taketo
Abstract : Timothy syndrome (TS) is a congenital long QT syndrome that is associated with syndactyly and mutations in CACNA1C, encoding an L‐type voltage‐dependent calcium channel, Cav1.2. Recently, TS has been associated with autism and other psychological disorders. This case indicated bradycardia by prenatal screening and was diagnosed as TS by the occurrence of syndactyly and QT prolongation at birth. Despite therapy with anti‐arrhythmia reagents and a pacemaker, the patient died 2 months after birth and was autopsied. The heart showed mild dilation and mild hypertrophy with a focal disarray pattern, which may be inconsistent with typical cardiomyopathy. Unexpectedly, bilateral adrenal glands showed marked shrinkage and severe fibrosis of the medulla with a small number of single‐strand DNA positive medullary cells and accumulation of hemosiderin‐containing macrophages. This finding suggests that CACNA1C mutation may induce drop‐out of medulla cells via apoptosis. This may be due to increased concentration of calcium ions consistent with Cav1.2 expression in adrenal glands as well as in the brain and the heart. This is the first report describing a systemic autopsy of TS with adrenal medullary dystrophy.